Navigating the Existential Crisis from Literature to Real Life: A Text-to-Self Pedagogical Approach and Its Potential for Existential Literature Instruction - Nhung Thi Hong Nguyen; Khoa Dang Truong (LET: Linguistics, Literature and English Teaching Journal)
Amidst the existential crisis in contemporary society, young individuals worldwide find themselves susceptible to self-inflicted harm or even self-destruction in response to their psychological ruptures and injuries, while lacking the requisite self-awareness and the patience to persevere on the journey of self-understanding. In this article, we draw upon Rosenblatt’s (1995) notion of Literature as Exploration to propound a text-to-self pedagogical approach to reading Haruki Murakami and Can Xue and to teaching contemporary existentialist literature. Comprising three strategies, namely The Art World in My Eyes, The Mind Film, and The Literary Conversation, this approach encourages students to engage deeply with the portrayal of death in the writers’ flagship novels that view death as an unwavering companion to young individuals’ life journey and growth. Based on Rosenblatt (1995), the three strategies, and our survey-based analysis of 2,000 Vietnamese high school students’ existential perceptions, we propose a model for literature instruction through promoting students’ transition from literary interpretations to self-discovery and self-realization of death associated with the existential crisis. This four-stage model, we expect, will get students poised to reconcile with their lost, solitary, and vulnerable ego, actively befriend their ‘inner child’, and develop into individuals with healed hearts and positive worldviews.